Psychological Impact of National Values on the Maturation of a Child's Personality (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article presents important aspects of the psychological impact of national values in the formation of a child’s personality. National values are considered to be significant elements that define the identity of a nation, reflecting its history and culture. They play a crucial role in shaping children’s identity by helping them understand the historical and cultural legacy of their country.